Incomplete exchange rate pass-through and hysteresis in trade: A survey of recent theories and an empirical study of export pricing of Finnish paper manufacturies - Jukka Vesala (Bank of Finland, 1992)
This paper analyzes factors affecting the pass-through from exchange rates to import prices. The prevailing market ·structure, product differentiation, intertemporal optimization and the role of expectations regarding the exchange rate are the elements whose explicit modelling enable the rationalization of the empirically observed incomplete and sluggish price response to exchange rate movements. Further, recent theories concerning hysteresis in trade prices and quantities are reviewed in order to demonstrate how large exchange rate changes may cause changes in market structure through foreign entry or exit, and/or changes in distribution capacity, and market share investments. These results are then applied to examine the dynamics of price adjustment, which is shown to be the slower the higher is the level of exchange rate uncertainty and the more significant ate the sunk investments required for market entry. An empirical study of export pricing of Finnish paper manufactures is carried out by estimating export price equations based on a mark-up pricing rule and a general error correction model as a dynamic empirical specification. The exchange rate pass-through estimates are significantly incomplete, also in the long run, and distinctly lower in exports to the USA than to West European markets. These results are generally consistent with the derived theoretical results. The huge appreciation of the US dollar during the first half of the 1980's seems to have evoked hysteretic effects in the US market for paper products as well as in Finnish exports to the USA, which show up as significant instabilities in the price equations. However, at the level of aggregate exports there is no clear evidence of such effects "following the devaluations of the Finnish mark in the observation period 1975-1991.
URN:NBN:fi:bof-201808021863
Keywords: 330